Effectiveness of H5P Interactive Video in Promoting the Development of Science Critical Thinking Skills - Edy Chandra; Kartimi Kartimi; Moh Sarjana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study was conducted to examine the effectiveness of H5P interactive videos in enhancing students’ critical thinking skills within an online biochemistry learning environment. A true experimental design employing a pretest-posttest control group model was utilized, involving two randomly selected third-semester student classes. The experimental group received instruction through H5P interactive videos, while the control group was taught using conventional methods. The findings revealed that the students who engaged with H5P interactive videos demonstrated significantly greater improvement in critical thinking skills compared to those in the control group. The mean critical thinking score of the experimental group was 80.08, exceeding the control group’s score of 66.08. The incorporation of interactive features such as embedded quizzes and real-time feedback within the H5P videos encouraged more active participation and deeper cognitive engagement, thereby fostering the development of critical thinking. The results of this study confirm that the integration of interactive digital technology into the learning process can substantially improve the quality of education, particularly in online settings. Furthermore, the implementation of H5P supports higher levels of student engagement and enables more personalized and adaptive learning experiences, both of which are essential for cultivating reflective and critical learners.Keywords: interactive video, H5P, critical thinking, science